ひまわり8号のデータを用いた積雪域識別の高精度化 - 余, 郷友祐; 井岡, 佑介; 谷川, 朋範; 保坂, 征宏; 青木, 輝夫; Yusuke, Yogo; Yusuke, Ioka; Tomonori, Tanikawa; Masahiro, Hosaka; Teruo, Aoki (2017)
第8回極域科学シンポジウム/個別セッション：[OM] 極域気水圏 12月5日（火）国立極地研究所 1階交流アトリウム The Eighth Symposium on Polar Science/Ordinary sessions: [OM] Polar Meteorology and Glaciology Tue. 5 Dec./Entrance Hall (1st floor), National Institute of Polar Research conference object